Prospects for the Use of Wine of Ukrainian Producers for Creation of Parapharmaceuticals - Kovalenko, S. M. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: The purpose of this paper is an analysis of raw materials stock and variety of Ukrainian wines, investigation of general chemical composition, and prospects for the use of wines of Ukrainian production for creation of new parapharmaceutical substances. Materials and Methods: Logical and analytical methods were used for the data analysis of the specialized literature and normative legal documentation related to the classification of types, variety, and chemical composition of wines that are available on the Ukrainian market. Research Results: The basic stock of raw materials, groups, and types of wines of the Ukrainian producers, chemical composition of red wine was analyzed, a comparative analysis of chemical composition of red and white wine was done. The data of the researches accomplished by us testify to topicality of the development for creation of new parapharmaceuticals on the basis of table red wine. Conclusions: On the basis of the fulfilled analysis, it was established that there is a sufficient stock of raw wine materials in Ukraine, the largest area (66.4%) is occupied by vineyards in the south of Ukraine, in particular, in Odessa, Kherson, and Mykolaiv regions. On the basis of the fulfilled analysis, for further research work, genuine wines with minimum content of sugar and alcohol (table and dry ones) made from the same grapes cultivar (ordinary), containing the highest amount of active substances that exhibited an antioxidant, anti-inflammatory, and regenerative effect in the agents under development and promoted the renewal and moisturizing of the skin, were selected.